2014
DOI: 10.1073/pnas.1406161111
|View full text |Cite
|
Sign up to set email alerts
|

Moving gating charges through the gating pore in a Kv channel voltage sensor

Abstract: Voltage sensor domains (VSDs) regulate ion channels and enzymes by transporting electrically charged residues across a hydrophobic VSD constriction called the gating pore or hydrophobic plug. How the gating pore controls the gating charge movement presently remains debated. Here, using saturation mutagenesis and detailed analysis of gating currents from gating pore mutations in the Shaker Kv channel, we identified statistically highly significant correlations between VSD function and physicochemical properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 70 publications
(100 reference statements)
0
60
0
Order By: Relevance
“…A previous study on bacterial stretch-activated ion channels proposed that wetting and dewetting of a hydrophobic region in the permeation pathway can play a major role in defining the thermodynamics and kinetics of mechanosensitive channel gating and can be the origin of hysteretic behavior (Anishkin et al, 2010). The hydration/wetting of the core of the Hv1 VSD appears to be an important requirement for proton conduction (Freites et al, 2006;Ramsey et al, 2010;Wood et al, 2012), and water penetration into the core of the channel's transmembrane module is believed to change considerably upon channel opening (Chamberlin et al, 2014(Chamberlin et al, , 2015Hong et al, 2014), especially in the proximity of the VSD charge transfer center or hydrophobic plug (Tao et al, 2010;Lacroix et al, 2014;Takeshita et al, 2014). So one possible origin for Hv1 mechanosensitivity could reside in changes of VSD wettability induced by membrane stretch, which would result in changes in the thermodynamic and kinetic properties of voltage-dependent gating (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study on bacterial stretch-activated ion channels proposed that wetting and dewetting of a hydrophobic region in the permeation pathway can play a major role in defining the thermodynamics and kinetics of mechanosensitive channel gating and can be the origin of hysteretic behavior (Anishkin et al, 2010). The hydration/wetting of the core of the Hv1 VSD appears to be an important requirement for proton conduction (Freites et al, 2006;Ramsey et al, 2010;Wood et al, 2012), and water penetration into the core of the channel's transmembrane module is believed to change considerably upon channel opening (Chamberlin et al, 2014(Chamberlin et al, , 2015Hong et al, 2014), especially in the proximity of the VSD charge transfer center or hydrophobic plug (Tao et al, 2010;Lacroix et al, 2014;Takeshita et al, 2014). So one possible origin for Hv1 mechanosensitivity could reside in changes of VSD wettability induced by membrane stretch, which would result in changes in the thermodynamic and kinetic properties of voltage-dependent gating (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Countercharge to S4 arginine residue interactions have been revealed with crystallographic data from Na V Ab, Na V Rh, and Na V Ms (Payandeh et al, 2011;Payandeh et al, 2012;Zhang et al, 2012;Sula et al, 2017;Wisedchaisri et al, 2019). It has also been hypothesized that negatively charged residues tune the hydrophilicity of the inner and outer vestibules of the VSD (Palovcak et al, 2014), while the central, hydrophobic region separates these vestibules and focuses the electric field (Starace and Bezanilla, 2004;Ahern and Horn, 2005;Chanda and Bezanilla, 2008;Lacroix et al, 2014).…”
Section: Structural Studies Illuminate Voltage Sensor Topology and Elmentioning
confidence: 98%
“…Their results showed that S4 arginines R1 and R2 move through a hydrophilic environment toward their interaction with phospholipid heads of the bilayer as the S2 ENC (D60)/S4 R3 salt-bridge interaction is formed with activation of the channel. The significance of hydration in voltage-gating is further emphasized with the finding that S4 aspartate substitutions in the Shaker channel are remarkably tolerated with respect to gating function (Diaz-Franulic et al, 2018), and by the corollary observation that mutation of S1-S3 residues comprising the hydrophobic plug have dramatic effects on gating charge movement (Lacroix et al, 2014, andreviewed by Bezanilla, 2018).…”
Section: Water Permeability Within and Across The Voltage Sensor Domainmentioning
confidence: 99%
“…In voltage-gated proteins, two distinct types of currents can be measured: 1) currents associated with the movement of the S4 segments, the so-called gating currents. This type of current is intrinsically transient, since the voltage sensor is anchored to the membrane, and difficult to detect, given the small amount of charge involved [6]; 2) currents associated with ion permeation, which have been investigated in cells of many organisms, including, for example, sponges [7,8] and mussels [9], marine [10,11] and aquatic [12] plants. These currents are modulated by a multitude of factors, i.e.…”
Section: Ion and Gating Currents Mediated By Ion-selective Channelsmentioning
confidence: 99%